Suitable Turbine Selection based on the Parameters of a Potential Site at Sarawak, Malaysia - Samo, K. A.; Samo, I. A.; Mughal, W.; Rigit, A. R. H.; Sohoo, A. A. (Engineering, Technology & Applied Science Research, 2020)
The tidal range is a renewable energy source. In Malaysia, most of the produced renewable energy is generated from the exploitation of the tidal range. The main purpose of this research is to determine a suitable system to produce tidal range energy from a potential site. A turbine selection chart is used. The mean tidal range of Kuching Barrage is 4.2m and the maximum flow rate over a gate is 226.9m3/s. Therefore, for the extraction of electrical power, a bulb-type turbine with a rated power of 5.2MW is identified as suitable to be deployed at the site.